The basic emotions in a tale: audiovisual perception in children - Etxebarria Lejarreta, Aintzane; Gaminde Terraza, Iñaki; Romero Andonegi, Asier; Iglesias Chaves, Aitor (Círculo de Lingüística Aplicada a la Comunicación, 2020)
The objective of this paper is to determine if linguistic selection coincides with visual selection when hearing an emotion. For that purpose, the story of Little Red Riding Hood was recorded, in which three basic emotions appeared, simulated by a young bilingual girl from the Basque Country. A specific test was designed for the study, in which 178 bilingual participants between the ages of 8 and 15 (99 male and 79 female), students of the third and fourth course of Primary Education and of the first and second in Compulsory Secondary Education from a state-assisted private school, had to choose the basic emotion that corresponded to what was heard. According to the results, linking the auditory stimulus relationship with the type of emotion verbalised is not complicated, creates contradictions, and seems to entail more difficulty for the subjects to link these with the visual stimuli
Keywords: basic emotions; audiovisual perception; prosody